Determination of Duchenne muscular dystrophy carrier status by single strand conformation polymorphism analysis of deleted regions of the dystrophin locus. Issue 12 (December 1991) - Richards, R I; Friend, K
Abstract : The molecular characterisation of the dystrophin gene, mutations in which are responsible for X linked Duchenne and Becker muscular dystrophies, has led to an array of strategies for the diagnosis of affected subjects and carriers. Initially these were based on blotting and hybridisation technologies but have recently been largely superseded by PCR based techniques which afford greater speed and sensitivity. We describe the use of single strand conformation polymorphism to detect heterozygosity in regions of the dystrophin locus which are deleted in affected males, to determine the carrier status of their female relatives.